The use of thyroid hormones in the treatment of euthyroid patients with treatment-resistant depression. Data from a survey of 5695 European national endocrine professional organization members - Ludgate, Stephen; McGowan, Anne; Moran, Carla; Attanasio, Roberto; Žarković, Miloš; Nagy, Endre Vezekenyi; Negro, Roberto; Papini, Enrico; Adler Cohen, Chagit; Akarsu, Ersin; Alevizaki, Maria; Ayvaz, Göksun; et al. (Frontiers in endocrinology, 2025)
PurposeTreatment-resistant depression (TRD) is most commonly defined as depression that has not responded to two different pharmacological agents used for an adequate period of time. We explored the views of European specialists via survey, regarding the use of thyroid hormone (TH) in euthyroid patients with TRD as part of ‘Treatment of Hypothyroidism in Europe by Specialists: An International Survey’ (THESIS).MethodsThe question “Thyroid hormones may be indicated in biochemically euthyroid patients with treatment resistant depression” was posed to specialists from 28 countries.Results5695 valid responses were received following 17,232 invitations (33.0% response rate; 65% female, 90% endocrinologists). 348 (6.1%) stated that TH may be indicated in biochemically euthyroid patients with TRD. This view was more common in males (p<0.01), respondents who saw ≥100 patients with hypothyroidism per year (p<0.01), respondents who worked in private practice (p=0.05) and respondents who were not members of international specialist associations (p=0.05). Geographical variation existed with respondents in Eastern Europe significantly more likely to use TH in TRD (p<0.01). Linear regression showed a statistically significant reduction in the use of TH for TRD with increasing gross national income (F-statistic=7.35, CI -0.15 - -0.02, p=0.01). TH in TRD was recommended in psychiatry guidelines but not endocrinology guidelines.ConclusionWhile there is limited evidence for their use, over 6% of respondents stated that TH may be indicated in TRD. Due to the risk of iatrogenic thyrotoxicosis and increased morbidity the use of TH should be addressed in relevant endocrinology guidelines and consensus should be reached between specialties.